AN ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS USED BY THE CHAK TRIBAL COMMUNITY OF BANGLADESH - Rana, Md. M.; Hossan, Md. S.; Hanif, A.; Rahmatullah, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The Chaks are a small tribal community inhabiting the Chittagong Hill Tracts forest region in southeastern Bangladesh. They are sometimes confused with the Chakmas, who form the largest tribal group in the region. Unlike the Chakmas, the Chaks have little association with settlers from outside their community. For curing of diseases, they rely on their own traditional medicinal practitioners, who serve as priests and experts on medicinal plants. Since little is known about the medicinal plants of this tribe, we conducted an ethnobotanical survey to learn more about their use of plants, which are quite diverse in the region. Interviews of Chak traditional healers were conducted in their own language and detailed information on usage of plant species to treat various ailments was noted. Plant specimens were photographed, collected and identified at the Bangladesh National Herbarium. A total of 47 plant species belonging to 31 families were collected. The major families included Leguminosae (five plants), Rubiaceae (four plants) and Asteraceae, Convolvulaceae and Labiatae families (three plants each). The diseases for which the various plants or plant parts were used included scabies, eczema, boils, abscess, ringworm, ear disorders, jaundice, stomach pain, intestinal worms, dysentery, bloating, acidity, constipation, throat ache, pneumonia, cough, mucus, tonsillitis, fevers and pains, urinary disorders like burning sensation during urination and frequent urination, as well as rheumatism, menstrual pain, vertigo, vomiting, toothache, wounds, bone fractures, impotency, tumor, cancer, snake, animal and insect bites, malaria, frequent thirsts, edema, kidney stones, allergy and elephantitis.